HYDROLOGIC REGIME AND MACROPHYTE ASSEMBLAGES IN TEMPORARY FLOODPLAIN WETLANDS: IMPLICATIONS FOR DETECTING RESPONSES TO ENVIRONMENTAL WATER ALLOCATIONS - Reid, Michael A.; Quinn, Gerry P. (Wetlands (Wilmington, N.C.), 2004)
This study describes the macrophyte assemblages of temporary floodplain wetlands situated on the floodplain of the Murray River, southeast Australia. Wetlands in the study are subject to flooding, the frequency, duration, and magnitude of which are dictated by the current, regulated river-flow regime. Our aim was to examine the influence of the existing flooding regime on macrophyte assemblages and to trial a monitoring program, based on a multiple before-after-control-impact (MBACI) design, to detect the impact of proposed environmental water allocations (EWAs) on the wetlands. Two categories of flooding regime were identified based on the flow magnitudes required for flooding to occur (flooding thresholds). In this scheme, wetlands with relatively low flooding thresholds are classed as ‘impact’ and those with higher thresholds are classed as ‘control.’ The wetlands were surveyed over a two-year period that incorporated at least one wetting-drying cycle at all wetlands. Results showed significant differences between survey times (season and year), but differences between flooding regime categories were significant only for some components of macrophyte assemblages. Differences between survey dates appear to reflect largely short-term responses to the most recent flood events. However, macrophyte differences observed between control and impact wetlands reflected the cumulative effect of flood events over several years. Differences between control and impact wetlands were strongest for post-flooding surveys based on full assemblages (using ANOSIM) and among specific taxa and functional groups (using ANOVA). Power to detect differences between control and impact wetlands was greatest for species richness and total abundance, but taxa with low variability among wetlands, and hence good power, were actually less sensitive to hydrologic change. We conclude that the MBACI design used in this study will be most effective in detecting wetland ecosystem responses to the implementation of EWAs if response variables are carefully chosen based on their sensitivity to hydrologic change.